Interaction of PARP2 with DNA structures mimicking DNA repair intermediates - Kutuzov, M.M.; Ame, J.-C.; Khodyreva, S.N.; Schreiber, V.; Lavrik, O.I. (Вiopolymers and Cell, 2011)
Poly(ADP-ribosyl)ation is a posttranslational protein modification significant for the genomic stability and cell survival in response to DNA damage. Poly(ADP-ribosyl)ation is catalyzed by poly(ADP-ribose)polymerases (PARPs). Whereas the role of PARP1 in response to DNA damage has been widely illustrated, the contribution of another DNA-dependent PARP, PARP2, has not been studied so far. Aim. To find out specific DNA targets of PARP2. Methods. The EMSA and the PARP activity tests were used. Results. We evaluated Kd values of PARP2-DNA complexes for several DNA structures mimicking intermediates of different DNA metabolizing processes and tested these DNA as «activators» of PARP1 and PARP2 in poly(ADP-ribose) synthesis. Conclusions. Like PARP1, PARP2 does not show correlation between the activation efficiency and Kd values for DNA. PARP2 was activated most effectively in the presence of over5DNA. Keywords: PARP1, PARP2, poly(ADP-ribosyl)ation, DNA binding.